Nascent Pre-rRNA Sorting via Phase Separation Drives the Assembly of Dense Fibrillar Components in the Human Nucleolus. - Yao, R. W.; Xu, G.; Wang, Y.; Shan, L.; Luan, P. F.; Wang, Y.; Chen, L. L.
Fibrillar centers (FCs)and dense fibrillar components (DFCs)are essential morphologically distinct sub-regions of mammalian cell nucleoli for rDNA transcription and pre-rRNA processing. Here, we report that a human nucleolus consists of several dozen FC/DFC units, each containing 2-3 transcriptionally active rDNAs at the FC/DFC border. Pre-rRNA processing factors, such as fibrillarin (FBL), form 18-24 clusters that further assemble into the DFC surrounding the FC. Mechanistically, the 5? end of nascent 47S pre-rRNA binds co-transcriptionally to the RNA-binding domain of FBL. FBL diffuses to the DFC, where local self-association via its glycine- and arginine-rich (GAR)domain forms phase-separated clusters to immobilize FBL-interacting pre-rRNA, thus promoting directional traffic of nascent pre-rRNA while facilitating pre-rRNA processing and DFC formation. These results unveil FC/DFC ultrastructures in nucleoli and suggest a conceptual framework for considering nascent RNA sorting using multivalent interactions of their binding proteins.
Keywords: FIBRILLARIN; GLYCINE- AND ARGININE-RICH; INTRINSICALLY DISORDERED REGION; RNA BINDING DOMAIN; RNA SORTING; NUCLEOLUS; CONDENSATES; RIBOSOMAL RNA; PHASE SEPARATION; SUPER-RESOLUTION MICROSCOPY